The Ponseti method for the management of congenital clubfoot patients at a training hospital in KwaZulu-Natal, South Africa. A retrospective observational study. - Barnes, Claudette Shirley Mandy; Keetse, Dr. Mmakgabo Matthews; Maré, Pieter Herman; Naidoo, Dr. Arushka; Rollinson, Dr. Paul Douglas; Ndimande, Dr. Nduduzo Siphesihle (Student’s Journal of Health Research Africa, 2026)
Background Clubfoot affects 1.55–6.93 per 1,000 live births in developing countries, making it a common congenital condition. However, awareness and knowledge of clubfoot management, particularly using the Ponseti method, remain limited in district and regional hospitals in rural South Africa. Objective This study examines the epidemiology, patient profile, clinical presentation, and Ponseti casting outcomes of congenital clubfoot at Ngwelezana Hospital to enhance understanding and optimize management of the condition. Methods A retrospective observational study was conducted at Ngwelezana Hospital in KwaZulu-Natal on patients’ records who visited the facility from January 2018 -June 2022. Data was collected on the profile of patients with congenital clubfoot deformity from the clinical records of patients attending the clubfoot clinic at Ngwelezana Hospital during this time. Results The median age of the cohort at presentation was 30.5 days (IQR: 7–92 days), with 58 % being seen in the first month and 25 % after three months. Males comprised 67% of the cases; bilateral deformities accounted for 61%. The mean initial Pirani score was 4.3 ± 1.4. The percutaneous Achilles tenotomy was enacted in 68.8 % of the infants. With biweekly casting, 8.3 % of feet never progressed to the bracing stage without surgical release. There were missed appointments among 12 % of families, and minor cast-related complications affected less than 4 % of casts. The completeness of data was compromised by 6.8 % missing outcome data. Conclusion Congenital clubfoot at Ngwelezana Hospital is treated with a modified Ponseti method. Delays, non-compliance, and socioeconomic challenges affect outcomes, highlighting the need for education and improved referrals. Recommendations Community education should be intensified for early detection, consequently decreasing the late presentation rate and compliance rate. Better data capturing, such as electronic, may add value to education, quality improvement, and further research on this topic.